A Case Report Of Kissing Carotid Arteries In The Retropharynx - Siti Asmat Md Arepen; Azreen Zaira Abu Bakar; Nour Hanan Daniah Mohd Bakhit; Ahmad Anwaar Muhammad Saifullah; Nor Azirah Salahuddin; Nor Eyzawiah Hassan (Vice-Chancellor for Research of Mashhad University, 2024)
Indexed by SCOPUS/ERA